Advances in technology and techniques for transcatheter aortic valve replacement with concomitant peripheral arterial disease - Wong, Chun-Ka; Chiu, Alston Conrad Ho-On; Chan, Kwong-Yue Eric; Sze, Shu-Yue; Tam, Frankie Chor-Cheung; Un, Ka-Chun; Lam, Simon Cheung-Chi; Tse, Hung-Fat (Frontiers in Medical Technology, 2022)
Aortic stenosis (AS) is a prevalent disease affecting 3.7% adult population aged 65 or above. In the past, surgical aortic valve replacement (SAVR) was the only definitive therapy available for treatment of severe AS. Owing to the invasive nature of open-heart surgery, patients with advanced age and frailty could not benefit from SAVR. The advent of transcatheter aortic valve replacement (TAVR) in the past decade offered an alternative treatment option for patients with severe AS, particularly those who are deemed to have high surgical risk. Nevertheless, a large proportion of patients also have concomitant peripheral arterial disease (PAD), which increases risk of peri-procedural vascular complication, as well as precluding possibility of transfemoral TAVR owing to inadequate luminal size for delivery system deployment. In this review, the prevalence and outcome of TAVR patients with lower extremities will be discussed. Furthermore, novel technologies and techniques that enable TAVR to be safely performed using transfemoral or alternative access in patients with severe PAD will be reviewed.